Prospects of Infrastructure Development in the Perspective of Economic Growth - Ardiansyah, Bagus; Kusmaryo, R. Dwi Harwin; Muin, Muhamad Fathul (Universitas Pendidikan Ganesha, 2020)
Infrastructure is one of the primary parts to drive economic growth. An area with adequate infrastructure will have good and stable economic growth. West Nusa Tenggara Province, as one of the disaster-prone areas, is facing significant problems in development, especially related to infrastructure and economic growth. After the disaster in 2018, the economy of West Nusa Tenggara Province has a sharp contraction to the negative value. Therefore, this study aims to analyze the prospects for infrastructure development to boost economic growth in the province of West Nusa Tenggara with panel data analysis. The results show that the infrastructures of electricity, water infrastructures, schools, health facilities, and capital expenditure have positive and significant effects on economic growth, while the length of the road has no significant effect. The effort to boost economic growth, the infrastructure development must be focused on the non-mining and non-quarrying sector. Also, areas with high earthquake potential must be considered to build earthquake-resistant infrastructure. For the road, it needs to improve the quality, just not the quantity.